Porphyrin Functionalization of CsPbBrI2/SiO2 Core–Shell Nanocrystals Enhances the Stability and Efficiency in Electroluminescent Devices. Issue 4 (19th December 2021) - Wahl, Jan; Engelmayer, Manuel; Mandal, Mukunda; Naujoks, Tassilo; Haizmann, Philipp; Maier, Andre; Peisert, Heiko; Andrienko, Denis; Brütting, Wolfgang; Scheele, Marcus
Abstract: Surface ligand exchange on all‐inorganic perovskite nanocrystals of composition CsPbBrI2 reveals improved optoelectronic properties due to strong interactions of the nanocrystal with mono‐functionalized porphyrin derivatives. The interaction is verified experimentally with an array of spectroscopic measurements as well as computationally by exploiting density functional theory calculations. The enhanced current efficiency is attributed to a lowering of the charging energy by a factor of 2–3, which is determined by combining electronic and optical measurements on a selection of ligands. The coupled organic–inorganic nanostructures are successfully deployed in a light‐emitting device with higher current efficacy and improved charge carrier balance, magnifying the efficiency almost fivefold compared to the native ligand. Abstract : Ligand exchange on all‐inorganic perovskite nanocrystals is performed with porphyrin‐based surface ligands. The interaction between nanoparticle and ligand results in an increased efficiency when deployed in light‐emitting devices due to an improved charge carrier balance and less quenching. This is attributed to a lowering of the nanocrystal charging energy.